HUBUNGAN ANTARA PELAKSANAAN IBADAH SHALAT DENGAN DISIPLIN BELAJAR SISWA IV MI MAMBA’UL HISAN RIMPIAN - Riska Khodijah; Denny Wahyuni; Nur Zakiyah (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2026)
This study aims to determine the relationship between the implementation of prayer worship and the learning discipline of fourth-grade students at Madrasah Ibtidaiyah Mamba’ul Hisan Rimpian. This study employed a survey method with a correlational approach and was categorized as descriptive quantitative research. The sampling technique used was purposive sampling, with a total sample of 21 students from class IV A. Data collection techniques were carried out through questionnaires and documentation. Data analysis used the Pearson Product Moment correlation test with the assistance of JASP. The results of the study indicated that there was a significant relationship between the implementation of prayer worship and students’ learning discipline. This was proven by the significance value of 0.001 < 0.05 and a correlation coefficient value of 0.703, which falls into the high correlation category. The findings showed that the better the students’ implementation of prayer worship, the better their learning discipline. The implementation of prayer worship can shape disciplined behavior because it trains students to be punctual, obedient to rules, and responsible in carrying out their daily obligations.